Compensatory proteome adjustments imply tissue-specific structural and metabolic reorganization following episodic hypoxia or anoxia in the epaulette shark (Hemiscyllium ocellatum) - Dowd, W. Wesley (American Physiological Society, 2010)
The epaulette shark (Hemiscyllium ocellatum) represents an ancestral vertebrate model of episodic hypoxia and anoxia tolerance at tropical temperatures. We used two-dimensional gel electrophoresis and mass spectrometry-based proteomics approaches, combined with a suite of physiological measures, to characterize this species' responses to 1) one episode of anoxia plus normoxic recovery, 2) one episode of severe hypoxia plus recovery, or 3) two episodes of severe hypoxia plus recovery. We examined these responses in the cerebellum and rectal gland, two tissues with high ATP requirements. Sharks maintained plasma ionic homeostasis following all treatments, and activities of Na(+)/K(+)-ATPase and caspase 3/7 in both tissues were unchanged. Oxygen lack and reoxygenation elicited subtle adjustments in the proteome. Hypoxia led to more extensive proteome responses than anoxia in both tissues. The cerebellum and rectal gland exhibited treatment-specific responses to oxygen limitation consistent with one or more of several strategies: 1) neurotransmitter and receptor downregulation in cerebellum to prevent excitotoxicity, 2) cytoskeletal/membrane reorganization, 3) metabolic reorganization and more efficient intracellular energy shuttling that are more consistent with sustained ATP turnover than with long-term metabolic depression, 4) detoxification of metabolic byproducts and oxidative stress in light of continued metabolic activity, particularly following hypoxia in rectal gland, and 5) activation of prosurvival signaling. We hypothesize that neuronal morphological changes facilitate prolonged protection from excitotoxicity via dendritic spine remodeling in cerebellum (i.e., synaptic structural plasticity). These results recapitulate several highly conserved themes in the anoxia and hypoxia tolerance, preconditioning, and oxidative stress literature in a single system. In addition, several of the identified pathways and proteins suggest potentially novel mechanisms for enhancing anoxia or hypoxia tolerance in vertebrates. Overall, our data show that episodic hypoxic or anoxic exposure and recovery in the epaulette shark amplifies a constitutive suite of compensatory mechanisms that further prepares them for subsequent insults.